Melastoma collinum - Tsen, S.; Mohd Yusof, Nur Adillah, M.Y.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Melastoma collinum is a small tree, endemic to Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 36 km2 and 6,782.7 km2, respectively. Although the AOO is calculated from known existing records, it is considered that the actual AOO may be considerably larger than this due to under sampling. It is a secondary species that can grow well in disturbed forest and, therefore, it is not considered to be affected by major threats. The species is known from several localities. Hence, it is assessed as Least Concern. Melastoma collinum is endemic to Sabah, Malaysia. It is known to occur in several districts, Beaufort, Keningau, Pensiangan and Tawau.